2015
DOI: 10.1111/aor.12599
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Multipotent Progenitor Cells on Polymethylpentene Membranes During Extracorporeal Membrane Oxygenation

Abstract: Multipotent progenitor cells were mobilized during pediatric extracorporeal membrane oxygenation (ECMO). We hypothesize that these cells also adhered onto polymethylpentene (PMP) fibers within the membrane oxygenator (MO) during adult ECMO support. Mononuclear cells were removed from the surface of explanted PMP-MOs (n = 16). Endothelial-like outgrowth and mesenchymal-like cells were characterized by flow cytometric analysis using different surface markers. Spindle-shaped attaching cells were identified early,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…In summary, our results indicate that ECMO support in ARDS is associated with increased MSC mobilization. This finding confirms the results of both Hoesli and Lehle et al who demonstrated the isolation of progenitor cells on ECMO membranes and within the ECMO circuit [11,13]. Our results also confirm those of Bui et al [46], who suggested, that ECMO increases the number of peripheral progenitor and stem cells.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In summary, our results indicate that ECMO support in ARDS is associated with increased MSC mobilization. This finding confirms the results of both Hoesli and Lehle et al who demonstrated the isolation of progenitor cells on ECMO membranes and within the ECMO circuit [11,13]. Our results also confirm those of Bui et al [46], who suggested, that ECMO increases the number of peripheral progenitor and stem cells.…”
Section: Discussionsupporting
confidence: 93%
“…Animal models of these diseases and experimental studies have demonstrated that EPC and MSC beneficially influence endothelial function and promote regeneration based on proangiogenic signaling [5,6,23,24]. In addition, previous studies suggest that ECMO support might increase the mobilization of EPC and MSC into the circulation [11][12][13]. Although ARDS patients in our study exhibited similar disease severity assessed by SAPS2 and TISS, subjects in the ECMO group showed increased numbers of the MSC subpopulations CD34 -/CD73 + / CD90 + and CD34 -/CD73 + /CD29 + /CD90 + in the disease course compared to the non-ECMO group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the detected small granular structures in the vicinity of nucleated cells represent either endothelial cells that stored vWF within the Weibel–Palade bodies, or PLAs. However, in vivo endothelialization of PMP‐gas exchange fibers during the ECMO therapy was excluded . Therefore, these structures represent PLAs consisting of platelets either cell membrane bound on or phagocytosed by leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…However, in vivo endothelialization of PMP-gas exchange fibers during the ECMO therapy was excluded. 9,21 Therefore, these structures represent PLAs consisting of platelets either cell membrane bound on or phagocytosed by leukocytes. Mostly, not only vWF but also P-selectin was found close to nuclei.…”
Section: Discussionmentioning
confidence: 99%